Case report: Clinical characteristics of anthrax meningoencephalitis: two cases diagnosed using metagenomic next-generation sequencing and literature review - Hu, Minzhe; Qiao, Xiaodong; Zhang, Jingliang; Qin, Danqing; Guo, Shougang; Zhao, Weili; Wang, Chunjuan (Frontiers in Medicine, 2025)
PurposeTo explore the clinical features, diagnosis, treatment, and prognosis of anthrax meningoencephalitis.MethodsThe clinical data of two cases of anthrax meningoencephalitis were summarized and the relevant literature was reviewed.ResultsBoth patients, who were farmers, had cutaneous lesions prior to the onset of meningoencephalitis. The clinical manifestations included fever (2/2), headache (2/2), stupor (2/2), meningeal signs (2/2), and lymph node enlargement (2/2). The CSF analysis showed erythrocytes, increased neutrophils, low glucose levels and high protein levels. CSF cytology revealed rod-shaped bacilli. Metagenomic next-generation sequencing of the CSF from both patients detected Bacillus anthracis. Additionally, cultures confirmed the presence of endogenous spores of macrobacteria. Brain imaging revealed subarachnoid hemorrhages and minimal cerebral edema. Despite aggressive antibiotic treatment, both patients died. Fifty-seven articles of the past 70 years were reviewed. There were 59 patients of anthrax meningoencephalitis in total, including 46 patients died. Stupor (42/46, 91.3% vs. 3/13, 46.2%, p = 0.001), agitation (15/46, 32.6% vs. 0/13, 0.0%, p = 0.043) and intracranial hemorrhage (37/46, 80.4% vs. 4/13, 30.8%, p = 0.002) were more common in the deceased group. Two types of bactericidal drugs or intrathecal injection drugs presented more often in the surviving group (10/13, 76.9% vs. 13/46, 28.3%, p = 0.001), whereas penicillin monotherapy presented more often in the deceased group (23/46, 50.0% vs. 2/13, 15.4%, p = 0.026).ConclusionAnthrax meningoencephalitis typically presents as a rapidly progressive bacterial meningoencephalitis. The occurrence of stupor, agitation and intracranial hemorrhage is possibly correlated with poor outcome. Two types of bactericidal drugs or intrathecal injection drugs are associated with better prognosis. Metagenomic next-generation sequencing can quickly and accurately detect B. anthracis in CSF.